(•)BMPO-OOH Spin-Adduct as a Model for Study of Decomposition of Organic Hydroperoxides and the Effects of Sulfide/Selenite Derivatives. An EPR Spin-Trapping Approach - Misak, Anton (Antioxidants (Basel), 2020)
Lipid hydroperoxides play an important role in various pathophysiological processes. Therefore, a simple model for organic hydroperoxides could be helpful to monitor the biologic effects of endogenous and exogenous compounds. The electron paramagnetic resonance (EPR) spin-trapping technique is a useful method to study superoxide (O(2)(•−)) and hydroxyl radicals. The aim of our work was to use EPR with the spin trap 5-tert-butoxycarbonyl-5-methyl-1-pyrroline-N-oxide (BMPO), which, by trapping O(2)(•−) produces relatively stable (•)BMPO-OOH spin-adduct, a valuable model for organic hydroperoxides. We used this experimental setup to investigate the effects of selected sulfur/selenium compounds on (•)BMPO-OOH and to evaluate the antioxidant potential of these compounds. Second, using the simulation of time-dependent individual BMPO adducts in the experimental EPR spectra, the ratio of (•)BMPO-OH/(•)BMPO-OOH—which is proportional to the transformation/decomposition of (•)BMPO-OOH—was evaluated. The order of potency of the studied compounds to alter (•)BMPO-OOH concentration estimated from the time-dependent (•)BMPO-OH/(•)BMPO-OOH ratio was as follows: Na(2)S(4) > Na(2)S(4)/SeO(3)(2−) > H(2)S/SeO(3)(2−) > Na(2)S(2) ~Na(2)S(2)/SeO(3)(2−) ~H(2)S > SeO(3)(2−) ~SeO(4)(2−) ~control. In conclusion, the presented approach of the EPR measurement of the time-dependent ratio of (•)BMPO-OH/(•)BMPO-OOH could be useful to study the impact of compounds to influence the transformation of (•)BMPO-OOH.